PENGEMBANGAN E-MODUL SIFAT FISIKA DAN KIMIA PERAIRAN BERBASIS RISET UNTUK MENSTIMULUS KEMAMPUAN BERPIKIR TINGKAT TINGGI MAHASISWA - Rahma Shafira, Anugra; Alwi, Wiwit; Nurhamidah, Nurhamidah (ALOTROP, 2023)
This research is a research-based e-Module development of the physical and chemical properties of waters that aims to determine the feasibility level and student response to the developed e-Module. This e-module uses the ADDIE development model limited to the development stage. The research was conducted at the Chemistry Education Study Program, University of Bengkulu with the research subjects being 37 students who had taken the Environmental Chemistry course in the 2022/2023 Academic Year. From the research results obtained (1) the level of feasibility of e-Modules in the material aspect was 91.4% while from the media aspect was 91.1%, therefore based on the results of validation by the validator, e-Modules are declared very feasible, (2) based on the results of the student response test, 87.2% are in the very good category. The ability of e-Modules to stimulate students' higher-order thinking skills is stated to be very good based on the results of validation tests and student responses related to the e-Modules developed on aspects of material on stimulus, learning activities, evaluation, and competency tests presented in the e-Modules. From the results obtained, it is known that the e-Module developed is feasible to use and be tested in lectures.